A Study of Lock-Free Based Concurrent Garbage Collectors for Multicore Platform - Hao Wu; Zhen-Zhou Ji (The Scientific World Journal)
Concurrent garbage collectors (CGC) have recently obtained extensive concern on multicore platform. Excellent designed CGC can improve the efficiency of runtime systems by exploring the full potential processing resources of multicore computers. Two major performance critical components for designing CGC are studied in this paper, stack scanning and heap compaction. Since the lock-based algorithms do not scale well, we present a lock-free solution for constructing a highly concurrent garbage collector. We adopt CAS/MCAS synchronization primitives to guarantee that the programs will never be blocked by the collector thread while the garbage collection process is ongoing. The evaluation results of this study demonstrate that our approach achieves competitive performance.